Green Tourism Development Using The Addie Learning Model In A Maqashid Sharia Framework At Gayo Highlands - Fitrah, Ramdansyah; Sukiman, Sukiman; Soemitra, Andri (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Balancing economic, social and environmental impacts in tourism management is a problem faced by the Gayo Highlands region. This research aims to reveal the development of green tourism in the Gayo Highlands using the ADDIE (Analyze, Design, Develop, Implement and Evaluate) learning model. The results showed that the development of green tourism in the Gayo Highlands could be done through 1) Environmental conservation, 2) Waste management and cleaning, 3) Renewable energy, 4) Use of sustainable transport, 5) Environmental education, and 6) Water and energy management for the environment responsibility component. For the experiential richness component, green tourism development can be done by 1) Knowledgeable tour guides, 2) Educational information, 3) Interactive experience, 4) Service quality, 5) Nature experience, and 6) Assessment of tourist satisfaction. For the cultural diversity component, green tourism development can be done through: 1) Promotion of cultural heritage, 2) Cultural tourism, 3) Cultural involvement in the local economy, 4) Respect for culture, 5) Counselling and education of tourists, and 6) Maintaining language heritage. As for the economic vitality component, green tourism development can be done through 1) Development of small and micro enterprises, 2) Providing training and education to residents, 3) Partnerships with local communities, 4) Local purchasing, 5) Local community involvement in planning, 6) Measuring social impacts. Through an approach that considers Maqashid Sharia, green tourism can be an effective means to achieve the goals of environmental protection, social welfare, and economic sustainability.